'ANÁΓKH - Pueo, Juan Carlos (Escritura e Imagen, 2006)
This article aims studying the tensions produced when adapting written texts for cinematic purposes. It is worth noting the 1937 cinematographic version of Notre Dame de Paris, in which Hugo describes the clash between oral and written cultures following the invention of the printing press. Dieterle’s film The Hunchback of Notre Dame revises Hugo’s reflections and adds some clues on the increasing clash between written and audiovisual cultures. Thus, the film offers a stereotypical writer´s image whereby the freedom of conscience ?usually associated with literature? is extended to cinema.